PROGRESSIVE CONTROL AND MANAGEMENT STRATEGIES IN THE ELIMINATION OF RABIES AMONG THE STRAY DOG (CANIS FAMILIARIS) POPULATION IN PAKISTAN - NAZAR, MW; REHMAN, FU; ASIF, H; HASHMI, HA; REHMAN, A; ARSHAD, M; HUSSAIN, K; SHAHZAD, M; ULLAH, Z; AWAIS, M (Biological and Clinical Sciences Research Journal, 2024)
Stray dogs are integrally linked with rabies transmission, and a sizeable unmanaged dog population hinders rabies control program planners. Dog population management (DPM) is one of the best strategies to control rabies transmission, improve health management, and lower the population size of stray dogs. The threat of rabies is very serious due to free-roaming dogs. Foxes, skunks, groundhogs, raccoons, and house bats are rabies vector species and can carry rabies virus without showing any symptoms. Rabies is a life-threatening disease that affects thousands of losses worldwide every year. World Rabies Day is an international awareness campaign coordinated by the Global Alliance for Rabies Control (GARC). In Pakistan, there are reportedly 3 million stray dogs. More than one million dog bite cases are reported annually throughout Pakistan. About 600 dog bite cases are reported daily in the Sindh province, Pakistan. Due to an uncontrolled number of stray dogs, many serious problems arise related to public health, socio-economic, and political issues. The Animal Act of 1890 provides a specific defense against cruelty and establishes its importance in Pakistani culture. Developing long-term and supportable strategies is imperative to overcome the stray animal population worldwide. To overcome the rabies issue in Pakistan, the government should implement projects on breeding control of stray dogs through spaying and neutering surgeries. The government should also provide proper shelters for dogs and rabies vaccines. There is a need to be aware of basic preventive measures such as disinfectants and rabies vaccination. Public awareness, rabies vaccination, and dog sterilization at the national level are crucial factors in preventing rabies and managing the dog population in Pakistan.